Characteristic parameter analysis of magnetic resonance diffusion tensor imaging in children with autism spectrum disorder: a retrospective study - Qianfang Jia; Xiaofang Wang; Xiwan Li; Shasha Li; Ming Wang; Luping Wang; Bingxiang Ma; Meng Zhang (BMC Pediatrics)
Abstract Background Magnetic resonance diffusion tensor imaging (DTI) has been widely used in research and clinical practice for neurological disorders, and plays an increasingly important role in the research of ASD. This study aimed to explore the parametric characteristics of DTI in children with ASD, which further may serve to guide the diagnosis. Methods Ninety children aged from 1 to 6 years old (male: female; 74:16) with ASD were selected to measure the parameters of fractional anisotropy (FA) and apparent diffusion coefficient (ADC) of the genu of corpus callosum, splenium of corpus callosum, frontal lobe, superior temporal gyrus in DTI. A 32-channel cranial nerve coil of a GE Signa HDxt 3.0T magnetic resonance system was used for the examination, and the FA and ADC maps were obtained by post-processing the DTI raw diffusion images with the Functool function software in the workstation. IBM SPSS 27.00 statistical software was used for statistical analysis. Results In ASD children, FA values for the genu of corpus callosum, splenium of corpus callosum, and superior temporal gyrus were higher on the right than on the left, and ADC values for the genu of corpus callosum, splenium of corpus callosum, frontal lobe, and superior temporal gyrus were lower on the right than on the left (P < 0.05). Grouped by sex, the female group had lower ADC values in the left splenium of corpus callosum and the right superior temporal gyrus than the male group (P < 0.05). Grouped by age, the left frontal lobe FA values were lower in the younger group (≤ 3 years old) than in the older group (>3 years old) (P < 0.05). Conclusion Quantitative parameters of DTI show that autistic children have a markedly lateralized development of the brain, with the right side developing better than the left, sex and age also affect brain development in ASD children, resulting in different characteristic parameters in DTI, which may provide a reference for the diagnosis of ASD.